Analisis Perbandingan Waktu dan Biaya Kelayakan Penggunaan Material Bata Ringan dan Sandwich PU Panel - Iwan Christianto (Pusat Riset dan Inovasi Nasional, 2024)
Construction projects are unique activities, many factors affect the uniqueness of construction projects, from the type of project, workers, the shape of the building, the budgeted costs to the environment where the construction project is built. The materials applied to construction projects are part of the uniqueness of construction projects that coincide with the environment and the type of project or in other words, the materials used in construction projects are very dependent on the cost and type of project, especially in wall installation, consisting of various materials, one of which is sandwich, PU panels, and light bricks. The application of materials also needs to be considered in the construction project that will be built, one example is the construction of a commercial broiler farm. This study aims to determine the comparison of time, cost, and difference in NPV value in wall installation using PU panel sandwich material and light brick in the construction of a commercial broiler farm in Wuryantoro, Wonogiri Regency, Central Java. Based on the results of the analysis, it was found that the time for wall installation with PU panel sandwich was 15 days, while the installation of walls with light bricks was 21 days for each building unit. And based on the RAB for the implementation of wall installation work using PU panels amounting to Rp. 666,246,585, and for the RAB for the implementation of wall installation with light brick materials worth Rp. 399,456,831. Meanwhile, for the comparison of NPV projected for 5 years for PU Panel is Rp. 244,981,275, while for light brick work it is Rp. 517,436,965. So that the difference in NPV between the two materials is Rp. 272,455,689.